AN EVALUATION OF PROMOTING STUDENT’S MORAL AND ETHICS PROJECTOF BAN NONG NAE SCHOOL - Ratsameekaew, Prakong (Journal of MCU Nakhondhat, 2022)
This research article aimed to 1) evaluate the context, 2) evaluate the inputs, 3) evaluate the process, and 4) evaluate the products. The research sampling contained 8 committee of Basic Education Organization and 117 people of parents and students in academic year 2564. For the research tools, the researcher employed index of item objective congruence (IOC) and reliability for the questionnaire. The statistics used for data analysis were average ( , m) and standard deviation (S.D.,s) The result of context evaluation related to teachers’ opinions was in the highest level Likewise, the result of committee’ opinions of Basic Education Organization was in high level Furthermore, the result of inputs evaluation from teachers’ opinion was in the highest level while the result of committee’ opinions of Basic Education Organization was also in the highest level Moreover, the result of process evaluation from promoting student’s moral and ethics project of Ban Nong Nae School showed that the teachers’ opinions were in high level and the committee’ opinions of Basic Education Organization were in high level as well For products evaluation of promoting student’s moral and ethics project of Ban Nong Nae School related to teachers’ opinions, it was found in high level as the same level as parents’ and students’ In addition, in the view of usefulness of products evaluation, the teachers’ opinions were in the highest level and the students’ opinions were also in the highest level It reveled that the students’ satisfaction of this project was in the highest level